اللجان الإدارية المتساوية الأعضاء في القانون الجزائري - محمد فوزي, مناعي (جامعة الوادي.University eloued, 2022)
" لقد شهد العالم ثورة في عالم التكنولوجيا و المعلوماتية وشبكات الإتصال , حيث قد مس هذا التطور جميع القطاعات من بينها قطاع الإدارات العمومية فحدثت بذلك تغييرا جذريا في أسلوب الإدارة و ظهر ما يعرف بالإدارة الإلكترونية أو الحكومة الإلكترونية, فتبنت معظم دول العالم هذا النظام من أجل تحسين و ترشيد الخدمة العمومية ومكافحة جميع المظاهر السلبية التي كانت ترافق الأسلوب التقليدي للإدارة من رشوة و بيروقراطية . وقد تأثرت الجزائر على غرار باقي دول العالم بهذا النظام الإداري الإلكتروني فانطلقت في مشروع الجزائر الإلكتروني و تبنت بذلك سياسة رقمنة القطاع العمومي ويظهر هذا في تسييرها للعديد من المرافق العمومية خاصة الخدماتية منها. وقد وضعت الأمم المتحدة عدة مؤشرات تنشرها ضمن تقارير دورية كل سنتين من أجل تقييم تجربة الإدارة الإلكترونية لكل دولة . هذا ويواجه تطبيق مشروع الجزائر الإلكتروني عدة عراقيل تسعى الحكومة الجزائرية لمواجهتها. ""Summary The word has reconized this last time , one revolusion very important In the domains : Technologie , computerscience and in the network of Technological development has touched all the sectors whose the public administration , This situation has changed the habitual practices of administration , It is appeared the electronic administration or the electronic govermment ; Now the majority of countries recognize this system what plus efficacity and rationality of administrative prestation against all the negative phenomenoms liked to traditional custoù of administration like corruption and bureaucrety. Insteed, Algeria has been touched by this technology like a nother countries of world, It launched in the project of electronic Algeria and has adapted a policy of numeration of public sector. This appears in his management at level of public infrastructures . The united states have created several index that are sent in the periodie reports all the two years for to assess the experience of electronic administration of avery country . The application of project electronic Algeria has met a number of obstacle that Algeria sceks to constram. Key words: Electronic administration - public infrastructure- electronic government - Network of communication – electronic project . "
ماستر قانون إداري
Keywords: اللجان الادارية-الأعضاء - المشرع الجزائري; Commissions administratives - membres - législateur algérien